Simulated serological data using serosim and subsequent results using the full mixture model on (a) HAI, (b) IgG and (c) IgM data with additional observational noise. - Marco Hamins-Puértolas (15238661) (2025)
For each we present the predicted infection status using the mixture model approach along with the true underlying infection status. Parameters chosen for forward simulation are presented in S1 Table and resulting metrics of accuracy are presented in S4 Table.